Cryptanalysis of Augmented Hill Cipher - Saeed, Rania; Bahig, Hatem M.; Nassr, Dieaa I. (Contemporary Mathematics, 2025)
The Augmented Hill Cipher (AHC) is a modified Hill Cipher that uses three secret keys and semi-cipher block chaining as its mode of operation. AHC is claimed to be secure. Recently, it has been used to obtain secure, fast, and loss-tolerant communication. In this paper, we present the first cryptanalysis of AHC. We show that AHC is vulnerable to two attacks: known-plaintext and chosen-plaintext attacks. The attacks are performed by introducing a new method to solve non-linear equations obtained by analyzing AHC. The attacks take place in polynomial time.